Marketing Mix Factors on Thai Tourists’ Behaviors in New Normal Tourism at Tourist Attraction of Mueang District, Ranong - Phomgate, Watcharin; Berndt, Pornnapat (Journal of Roi Et Rajabhat University, 2023)
The objective of this research was to investigate the Marketing Mix Factors that influence the new normal tourism behavior of Thai tourists in Mueang Ranong District, Ranong Province. This study employed a quantitative research approach, utilizing questionnaires as the data collection tool. The gathered data were analyzed using a statistical program, employing descriptive statistics including percentage, mean, standard deviation, and multiple regression analysis with the Enter technique. The behavior of tourists in the new normal tourism setting was elucidated using a confidence level of 95%. The findings revealed that Regarding the assessment of Marketing Mix Factors in the context of new normal tourism among Thai tourists in Mueang Ranong District, Ranong Province, the overall opinion level was found to be the highest. When examining each aspect, it was observed that the factors with the highest average values were process, followed by physical evidence, people, product, place, price, and promotion. The results of the hypothesis testing demonstrated that several Marketing Mix Factors significantly influence the new normal tourism behavior of Thai tourists in Mueang Ranong District, Ranong Province. Specifically, product, price, place, people, process, and physical evidence exhibited statistical significance at the 0.05 level. However, in the context of the COVID-19 crisis, marketing promotion was found to have no effect on new normal tourism behavior.